Indian children carrying home water; Trinidad, B.W.I. - (:unkn) unknown (Wilson and Johnstone, Trinidad [Printed in Scotland by Robert MacLehose and Co. Ltd.], 2008)
Photo of two East Indian children carrying water buckets. Number J365. Includes an United States one cent postage stamp dated April 17th 1951.
Colour: Black and White; Style: Portrait; Other: Unbordered, Divided
Addressed to Master Billy Moyka, St. Bernards School, Gladstone, New Jersey
Keywords: Postcards; Trinidad and Tobago; East Indians--Trinidad and Tobago; Children--Trinidad and Tobago; 1951; Indian boys--Trinidad and Tobago; Indian girls--Trinidad and Tobago; Boys--Trinidad and Tobago; Girls--Trinidad and Tobago; Pails--Trinidad and Tobago; Chores--Trinidad and Tobago